Complete amino acid sequence of variable domains from two monoclonal human anti-gamma globulins of the Wa cross-idiotypic group: suggestion that the J segments are involved in the structural correlate of the idiotype. - Andrews, D W (1981)
The complete amino acid sequences of the variable regions of two human IgM anti-gamma globulins are reported. The two proteins, Sie and Wol, share idiotypic determinants that are distinct from those shared by the two previously sequenced IgM anti-gamma globulins, Lay and Pom [Capra, J. D. & Kehoe, J. M. (1974) Proc. Natl. Acad. Sci. USA 71, 4032-4036; Klapper, D. G. & Capra, J. D. (1976) Ann. Immunol. (Inst. Pasteur) 127C, 261-271.] In contrast to Lay and Pom, Sie and Wol have very little homology in the complementarity-determining hypervariable regions of either their light or heavy polypeptide chains. However, there are only two amino acid differences in the framework portions of the light chains, and the J segments of both chains are homologous. These data suggest that the predominant idiotypic determinant in this cross-idiotypic system may be different than in the Po group and may be either related to their light chain framework structures or to the amino acid sequence in the J segments of these molecules.